Test pilots - Späte, Wolfgang 1911-1997; Tindall, David 1936- (Independent, 1999)
From the first tests ofparachutes, to rocket-propelled explosive gliders, to the 'ground effect' flying boat, Test Pilots is a unique and absorbing collection of aviation stories. Over a period of many years, the author collected the memoirs and papers of pilots, from the very earliest years of aviation to the modern test pilot age. Test Pilots highlights the writings of Kurt Zwickau, Hanna Reitsch, Jean Marie Saget, and other renowned aviators.